Recovery from a cycling time trial is enhanced with carbohydrate-protein supplementation vs. isoenergetic carbohydrate supplementation - Berardi, J. M.; Noreen, E. E.; Lemon, P. W. R. (Journal of the International Society of Sports Nutrition, 2008)
In this study we assessed whether a liquid carbohydrate-protein (C+P) supplement (0.8g/kg C; 0.4g/kg P) ingested early during recovery from a cycling time trial could enhance a subsequent 60 min effort on the same day vs. an isoenergetic liquid carbohydrate (CHO) supplement (1.2g/kg).